BIOCHEMICAL OXYGEN DEMAND—ITS CHEMICAL REACTION, MATHEMATICAL INTERPRETATION AND METHODOLOGY - Basu, A K (Indian Journal of Fisheries, 2011)
ANY one who studies water pollution and industrial effluents comes acrossthe ever important three words—^Biochemical Oxygen Demand, which meansthe amount of oxygen, in mg., taken up by 1 litre of the sample (usuallydiluted with sufficient well-oxygenated tap-water or synthetic dilution watermade by aerating the distilled water and adding the nutrient salts) or thequantity of dissolved oxygen required to effect stabihsation by aerobic bacterialaction that portion of the dissolved organic matter which can be oxidised in5 days at 20° C. It has been observed that in India, Germany and U.S.A.' the usual practice is to do B.O.D, tests at 20° C. (68° F.) but in England mostof the B.O.D. experiments are done at 18-3° C. (65° F.) even though this isgiving way to 20° C. rapidly. But in practice and interpretation the experimentis not so simple as that. In the present paper a comprehensive attemptto explain the basic methodology, chemistry and kinetics involved in B.O.D.experiment will be made.